The Promotion Strategy in Batu Jato Ecotourism in Sekadau Regency - Goreti, Goreti; Kurniati, Dewi; Oktoriana, Shenny (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol 14 No 2 (2020): Vol.14.No 2, 2020DO - 10.24843/SOCA.2020.v14.i02.p09, 2020)
Batu Jato is a tourist attraction site that frequently visited by local tourists on Sundays or public holidays. Batu Jato ecotourism has natural beauty views, clear river water, and vast expanse of rocks along the river. The descriptive, quantitative, and qualitative method was employed to obtain the primary and secondary data used in the study. Thirty participants were working as the village office staff, tourism department, tourism object management parties, tourists, and community around the Batu Jato ecotourism. The data collection is done by interview and questionnaire. The data analysis was conducted by SWOT analysis and Quantitative Strategic Planning Matrix (QSPM) analysis. There were three strategies arranged from SWOT analysis: 1) implementing a collaboration between the tourism object management parties, village office staff, and tourism department through an exhibition, souvenirs, banners, brochures, and pamphlets describing the Batu Jato attraction sites; (2) implementing a verbal communication as a method to deliver information about the Batu Jato attraction site such as through tourism extention and direct communication; and (3) improving the Batu Jato Ecotourism promotion through social media platforms such as website, Facebook, Instagram, WhatsApp and Youtube using attractive content in the form of pictures and writings.